The Effectiveness of Acceptance and Commitment-Based Therapy on the Immune Function and Activity Limitations in Patients With Irritable Bowel Syndrome - Sepideh Shakernejad; Javad Khalatbari; Majid-Mahmoud Alilou (Guilan University of Medical Sciences, 2021)
Introduction: Irritable bowel syndrome is the most common, costly, and disabling dysfunction of the gastrointestinal tract. Mental disorders can be one of the main factors in the onset, continuation, or exacerbation of gastrointestinal signs and symptoms in people with this syndrome. Commitment and acceptance therapy is a mixture of four approaches of awareness, acceptance, commitment, and behavior change, and its overall goal is to achieve psychological flexibility to move towards thought-based behavior. This treatment focuses less on reducing symptoms and more on improving the quality of life. Objective: This study aimed to determine the effectiveness of acceptance and commitment-based therapy on the immune function and activity limitations in patients with irritable bowel syndrome. Materials and Methods: This study was a quasi-experimental research with a pre-test, post-test design and a control group. Thirty patients with irritable bowel syndrome were randomly selected from those referred to a hospital clinic in Tabriz City, Iran. They were randomly divided into the intervention and control groups (15 in each group). The intervention group received acceptance and commitment group therapy for 8 sessions, while the control group did not receive any intervention. Both groups were assessed before and after the intervention, and in the follow-up phase using the activity limitations subscale of quality of life questionnaires (to measure activity limitations) and stool calprotectin test to assess safety performance. Data analysis was performed using descriptive statistics indices (mean and standard deviation) and analysis of variance with repeated measures, Bonferroni test, and analysis of covariance to test the study hypotheses. Results: The Mean±SD age of the intervention group was 34.53±18.38 years, and the Mean±SD age of the control group was 42.80±17.97 years. The significance levels of Levene's and the Shapiro-Wilk test for all variables were greater than 0.05. Based on the results, the Mean±SD score of the activity limitations variable in the intervention group was 7.53±4.24 in the pre-test, 17.66±3.41 in the post test, and 17.26±3.65 in the follow-up. According to the results, activity limitations (P=0.027) and safety performance (P=0.034) were significantly different before and after the intervention. Conclusion: The present study's findings show that acceptance and commitment-based therapy can play an influential role in improving patients' immune function and promoting their activity limitations. Therefore, this treatment is recommended as a complementary therapy in patients with irritable bowel syndrome.